Increase in the Productivity of PS-Converters at Saganoseki Smelter & Refinery - Masatoshi Maeda; Yushiro Hirai; Fumio Hashiuchi; Toshihiro Nagata (The Minerals, Metals and Materials Society, 2000)
"Increase in the copper smelting capacity at Saganoseki Smelter & Refinery was attained through various improvements in the PSconverters and the flash furnace. Two of the major innovations in the converting process were: a new operational technology which avoids increase in the copper content in the converter slag even when higher copper grade matte (65%) are treated in the slag making stage and a technology which shortens the operational interruption time which is caused by coolant charging. The latter was realized by introducing a new automated coolant charging system with which it was made possible to charge the coolant without stopping the blowing into the converter. These improvements brought about a remarkable increase in · the production capacity per converter and an annual production of 450,000 tons of copper without adding new furnaces was made possible. In addition, good results have been obtained of the tests with modified tuyeres to further increase the production.IntroductionIn a bid to renovate its Saganoseki Smelter & Refinery and to establish a leading production unit in terms of global competitiveness, Nippon Mining & Metals undertook major restructuring efforts since 1994. One of its themes was the shift from· a two-flash furnaces operation to a single-flash furnace operation. The shift was successfully completed in 1996 while maintaining the production at the same level (330,000 tons per annum of copper). Then, the productivity was enhanced to 450,000 mtpy without adding new furnaces through technological and operational improvements. It is now planned to increase the smelting capacity further to 470,000 mtpy this year.Some technological and operational improvements in the matte converting process and the new plan resulted from the tests with modified tuyeres are presented in this paper."